2016
DOI: 10.1007/s00382-016-3355-5
|View full text |Cite
|
Sign up to set email alerts
|

Projection of temperature and heat waves for Africa with an ensemble of CORDEX Regional Climate Models

Abstract: Horn of Africa may have values of HWMId larger than that of longer, but relatively weak, heat waves over West Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 53 publications
11
93
0
Order By: Relevance
“…A complete discussion of the technique, including validation and effect on climate indices can be found in Piani, Haerter et al (), Dosio and Paruolo (), and Dosio et al (). Dosio () showed that bias‐adjustment largely improves the value of present and future threshold‐based indices (e.g., the number of summer days): these indices are generally poorly simulated over the present climate, such that the projected climate change may not be reliable. The climate change signal of percentile‐based indices (e.g., Tx90p) and indices related to the duration of an event (e.g., warm spell duration) are not affected by bias‐adjustment (Dosio, ).…”
Section: Methodsmentioning
confidence: 99%
“…A complete discussion of the technique, including validation and effect on climate indices can be found in Piani, Haerter et al (), Dosio and Paruolo (), and Dosio et al (). Dosio () showed that bias‐adjustment largely improves the value of present and future threshold‐based indices (e.g., the number of summer days): these indices are generally poorly simulated over the present climate, such that the projected climate change may not be reliable. The climate change signal of percentile‐based indices (e.g., Tx90p) and indices related to the duration of an event (e.g., warm spell duration) are not affected by bias‐adjustment (Dosio, ).…”
Section: Methodsmentioning
confidence: 99%
“…We set our regional focus over the African continent as Africa is supposed to be a climate change hot spot with a high exposure to future climate changes and a low adaptation capacity resulting in a very large vulnerability to future climate change (e.g., Intergovernmental Panel on Climate Change Fifth Assessment Report). and have been analyzed and published in coordinated ways within the CORDEX-Africa initiative (e.g., Abba Omar & Abiodun, 2017;Abiodun et al, 2017;Diallo et al, 2016;Dosio, 2017;Dosio & Panitz, 2016;Fotso-Nguemo et al, 2017;Pinto et al, 2016;Sylla et al, 2016). Examples are the widely spread rainfed agricultural systems, the fragile infrastructure, and various health issues related to climate such as malnutrition after droughts, heat waves (HWs), but also malaria outbreaks (e.g., Kjellstrom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such temperature increase is expected to continue in the future with a projected global temperature change of about 1.4°C to 4.8°C (Intergovernmental Panel on Climate Change, 2014) and a regional response over the Sahel of about 2°C to 6°C (Sylla, Nikiema, et al, 2016) when considering the Representative Concentration Pathway 4.5 and 8.5 concentration scenarios (Moss et al, 2012). As a result, hot extremes will become more common and deadly in many regions across the world (Gasparrini et al, 2017;Im et al, 2017;Lee & Kim, 2016;Mora et al, 2017) and in tropical Africa (Giorgi et al, 2014;Liu et al, 2017;Russo et al, 2014), with their frequency, duration, and magnitude depending on the underlying forcing scenario (Anderson et al, 2018;Dosio, 2017;Linares et al, 2014;Russo et al, 2016). Such hot extremes can have widespread impacts on human and natural systems, thereby challenging the adaptive capacity and resilience of local populations and activities (Ceccherini et al, 2017;Fontaine et al, 2013;Pal & Eltahir, 2016;Sultan & Gaetani, 2016;Zougmoré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%